Spatially and temporally controlled hydrogels for tissue engineering - Leijten, Jeroen; Seo, Jungmok; Yu, Kan; Trujillo-de Santiago, Grissel; Tamayol, Ali; Ruiz-Esparza, Guillermo U.; Shin, Su Ryon; Sharifi, Roholah; Noshadi, Iman; Moises Alvarez, Mario; Zhang, Yu Shrike; Khademhosseini, Ali (ELSEVIER SCIENCE SA, 2017)
Recent years have seen tremendous advances in the field of hydrogel-based biomaterials. One of the most prominent revolutions in this field has been the integration of elements or techniques that enable spatial and temporal control over hydrogels' properties, and functions. Here, we critically review the emerging progress of spatiotemporal control over biomaterial properties towards the development of functional engineered tissue constructs. Specifically, we will highlight the main advances in the spatial control of biomaterials, such as surface modification, microfabrication, photo-patterning, and bioprinting, as well as advances in the temporal control of biomaterials, such as controlled release of molecules, photocleaving of proteins, and controlled hydrogel degradation. We believe that the development and integration of these techniques will drive the evolution of next-generation engineered tissues. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: STEM-CELL FATE; HYALURONIC-ACID HYDROGELS; DOUBLE-NETWORK HYDROGELS; SKELETAL-MUSCLE TISSUE; HIGH-THROUGHPUT; IN-SITU; DRUG-DELIVERY; PHOTODEGRADABLE HYDROGELS; POLY(ETHYLENE GLYCOL); ALGINATE HYDROGELS